2016
DOI: 10.1109/jphotov.2016.2559785
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating Dilute-Tin Alloy SiGeSn for Use in Multijunction Photovoltaics: Single- and Multijunction Solar Cells With a 1.0-eV SiGeSn Junction

Abstract: SiGeSn ternary alloys offer a means to fabricate a 1.0-eV subcell junction for inclusion in a multijunction solar cell. The main advantage of the SiGeSn alloy is a tuneable bandgap energy and variable lattice parameter, enabling the material to be integrated into the existing lattice-matched multijunction architectures. Recent growth, structural, optical, and device results from SiGeSn material, with energy gaps in the vicinity of 1.0 eV and lattice matched to Ge substrates, are presented. An all latticematche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Initially, the SiGeSn alloys were grown with an ultra-high vacuum CVD on 4-inch Ge (100) substrates, with a miscut of 6° towards the <111> plane to reduce the formation of anti-phase boundaries in the subsequent MOCVD growth [6]. Before the 1.0 eV SiGeSn layer, a highly doped SiGeSn acting as back surface field was grown in order to limit the diffusion of minority carriers into the Ge inactive substrate [5]. The SiGeSn subcell was p-type doped to lxlO 18 cm" 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the SiGeSn alloys were grown with an ultra-high vacuum CVD on 4-inch Ge (100) substrates, with a miscut of 6° towards the <111> plane to reduce the formation of anti-phase boundaries in the subsequent MOCVD growth [6]. Before the 1.0 eV SiGeSn layer, a highly doped SiGeSn acting as back surface field was grown in order to limit the diffusion of minority carriers into the Ge inactive substrate [5]. The SiGeSn subcell was p-type doped to lxlO 18 cm" 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the development of this new alloy is still in its infancy, materials research is progressing and the first prototypes of operating devices have been reported [5]. Here, the characterization of a set of single and multijunction solar cells incorporating SiGeSn active junctions is presented.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows a possible fully lattice-matched device architecture consisting of InGaP/(In)GaAs/SiGeSn/Ge. Although functional single and triple-junction devices containing SiGeSn have been demonstrated [13], design of a high-quality 4J cell requires further insight into the fundamental properties of SiGeSn at various compositions, and high-quality material growth at the desired composition.…”
Section: Label Energy (Ev)mentioning
confidence: 99%
“…Si x Ge 1−x−y Sn y ternary alloys have been a topic of research interest for a variety of applications, including group IV lasers [1,2], photodiodes [3], light-emitting diodes (LEDs) [4,5] and photovoltaics [4,[6][7][8]. By controlling the alloy composition, it is possible to tune the bandgap, higher-energy interband transitions, and the lattice constant.…”
Section: Introductionmentioning
confidence: 99%